Analysis Proton Conducting Electrolyte IT-SOFC Hybrid System Exhaust Gas With External Reforming of Biofuel - Nizar Amir; I.N.G. Wardana (Chemistry Department, The University of Brawijaya, 2013)
In this analysis, a hybrid system containing proton SOFC (P-SOFC) combine with micro gas turbine (MGT) with biofuel external reforming is investigation to decrease the greenhouse gases problem facing in electrical power plant. The hybrid system consist of a proton solid oxide fuel cell stack, a micro gas turbine, a combustor, compressors, heat exchangers and external reformer. The main operating parameter such as, fuel utilization and steam - carbon ratio is determined in this analysis.